Assessing the implementation of the government funded community health worker programme in selected clinics of the Eastern Cape Province, South Africa - Matwa, Princess Nonzame (University of the Western Cape, 2013)
Magister Public Health - MPH === From 2004 the Eastern Cape Department of Health (ECDoH) started implementing the new community health worker (CHW) programme in all its clinics, but so far little is known about its implementation process, its successes and challenges. The aim of this study was to assess the implementation of the new government funded CHW programme at three clinics of the Eastern Cape Province. === South Africa